2006
DOI: 10.13182/nt156-332
|View full text |Cite
|
Sign up to set email alerts
|

Review of Literature on Ruthenium Behavior in Nuclear Power Plant Severe Accidents

Abstract: During a hypothetical severe accident in a pressurized water reactor (PWR), fission products (FPs) are released from the nuclear fuel and may reach the reactor containment building. Among the FPs, ruthenium is of particular interest due to its ability to form volatile oxide compounds in highly oxidizing conditions. In addition, ruthenium is a very hazardous compound because it is chemically toxic and also because of its radiotoxicity. The topic of ruthenium is examined in terms of nuclear safety issues. A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…However, a copper-ruthenium compound could be identified on the copper samples analyzed with XRD, samples 9-Cu and T3-Cu -copper(II)-hydroxo-oxoruthenate(VI) (CuRuO 2 (OH) 4 ). This copper-ruthenium compound is an orthorhombic compound first discovered by Nowgorocki [24] and later characterized by Hansen [25].…”
Section: Xrd Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a copper-ruthenium compound could be identified on the copper samples analyzed with XRD, samples 9-Cu and T3-Cu -copper(II)-hydroxo-oxoruthenate(VI) (CuRuO 2 (OH) 4 ). This copper-ruthenium compound is an orthorhombic compound first discovered by Nowgorocki [24] and later characterized by Hansen [25].…”
Section: Xrd Measurementsmentioning
confidence: 99%
“…The CuRuO 2 (OH) 4 compound is rather unknown [25] and has not been analyzed with the ESCA method, i.e. no ESCA data on CuRuO 2 (OH) 4 are available. However, the dissimilarity between the two methods might be caused by the difference in thickness of analysed surface layer.…”
Section: Xrd Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ruthenium is a fission product, its volatility has been studied in the context of the dissolution of spent nuclear fuel in nitric acid [14,15] and of nuclear power plant severe accidents (for a recent review see [16]). In particular it has been shown that the vapour of ruthenium dioxide in air contains significant amounts of RuO 3 and RuO 4 (e.g., under thermodynamic equilibrium at 1100°C and 1 bar pressure: 2 wt% RuO 3 and 0.2 wt% RuO 4 [17]).…”
Section: Introductionmentioning
confidence: 99%